The influence of corporate social responsibility on safety behavior: The importance of psychological safety and the authentic leadership - Kim, Byung-Jik; Kim, Min-Jik; Lee, Julak (Frontiers in Public Health, 2022)
Considering the importance of safety behavior, the current study investigates the relationship between CSR and safety behavior. To be specific, we delve into the underlying mechanism and its contingent factor of the association. This paper proposes that CSR promotes employee safety behavior through the mediation of psychological safety. In addition, authentic leadership may function as a positive moderator that amplifies the positive effect of CSR on psychological safety. Utilizing 3-wave time-lagged survey data from 213 South Korean workers, the current study empirically tests the hypotheses by establishing a moderated mediation model by utilizing structural equation modeling. The results demonstrate that CSR enhances employees' safety behavior by increasing their psychological safety and that authentic leadership positively moderates the relationship between CSR and psychological safety. This research's findings have meaningful theoretical and practical implications.